MINIMAX ALGORITHM BASED ON "MAIN INI YUK" GAME - Sirajuddin Hawari; Muhammad Zulfikri Maulanab; Teuku Binzar Nawaf Musyaffa; Desy Komalasari; Mutiara Persada Pulungan (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2022)
In the game there are rules for each game. The rules are made as a challenge to achieve victory. To achieve victory requires analysis of the right algorithm in making decisions. Minimax is one of the best decision-making algorithms to be applied in a game. The time complexity of the minimax algorithm is O(b^m) which b is the branching and m is the depth.